Pete the cat five little pumpkins - Dean, James 1957- (HarperCpllins Children's Books, an imprint of HarperCollinsPublishers, 2015)
Join Pete the Cat as he rocks out to this cool adaption of the classic Halloween song "Five little pumpkins."